Pengaruh High Intensity Interval Training Terhadap Perubahan Cardiorespiratory Fitness Pada Remaja Overweight (Studi Literatur) - Mohammad Ali; Erna Sariana; Nur Amelza Wahyu Aqilla (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2021)
The incidence of overweight adolescents reach 6.8% of the world's population and has an impact on cardiorespiratory fitness. High-intensity interval training is a interval training which can stimulate cardiac contractility. Purpose: To determine the effect of high-intensity interval training on changes in cardiorespiratory fitness in overweight adolescents. Methods: The design of this study is a literature study with literature finding from 4 databases (PubMed, Sciencedirect, Semantic Scholar, and Sage Journal) Results: There are significant differences after high intensity interval training on cardiorespiratory fitness changes in overweight adolescent from 8 literatures with training’s variation using cycling, walking, and running and measuring the outcome with treadmill with gaz analyzer, run with gaz analyzer, astrand cycle test, and yo yo intermittent endurance test. Conclusion: High intensity interval training has an effect on cardiorespiratory fitness changes in overweight adolescents.